Human Values Model Analysis on Organizational Commitment in Higher Education - Mahmud, Amir; Susilowati, Nurdian; Tusyanah, Tusyanah (JDM (Jurnal Dinamika Manajemen), 2019)
This study aims to test the human values model in order to determine satisfaction, values, work motivation, and organizational commitment of lecturers at the Faculty of Economics, UNNES. The population are all employees (BLU, CPNS, and PNS) of UNNES. By using propotinate random sampling, there are 323 employees as research sample. Furthermore, data is collected by questionnaire and analyzed by path analysis. The data wereÂ  collected using questionnaires, then were analyzed using path analysis. The results of the study were. firslyt, satisfaction with remuneration and work motivation could directly influence organizational commitment. Secondly, work motivation successfully mediated the influence of values on organizational commitment. Different things showed that satifaction with remuneration had no influence on organizational commitment when mediated by work motivation